Optically transparent and refractive thiol-ene polymers containing cyclotriphosphazenes - Jin, Jeong-Un; Lee, Miyeon; You, Nam-Ho (WILEY, 2024)
A colorless, transparent thiol-ene polymer network was developed that contains cyclic phosphazene units in the polymer chain. Hexakis (allyloxy) cyclotriphosphazene (HAP) was synthesized from the nucleophilic substitution reaction of phosphonitrilic chloride trimer and allyl alcohol. Thiol-ene polymers (HAP-SH) were successfully prepared without by-products or the use of solvents through photopolymerization of the HAP and multithiol monomers with various functional group and flexible structures (e.g., 1,4-butanedithiol (BDTH), 1,3,5-benzenetrithiol (BTTH), trimethylolpropane tris (3-mercaptopropionate) (TTMP) and pentaerythritol tetrakis (3-mercaptopropionate) (PTTH)). The prepared HAP-SH polymers showed sufficient thermal stability due to the high degree of cross-linking. In addition, the HAP-SH polymer films exhibited high optical transparency of over 90% in the visible region. The refractive indices of the HAP-SH polymers measured at 637 nm were in the range of 1.5530-1.6344, and the Abbe number was calculated to be in the range of 34.5-47.1. These results are attributed to the structure of the cyclophosphazine and the polymer main chain containing aliphatic linkers with sulfur atoms. Another significant result was the transparency of the HAP-SH polymer films in the mid-infrared (MWIR) region. The thermal stability and excellent optical properties of the HAP-SH polymers make them good candidates for application as a protective film for IR lenses, which are easily damaged by external factors. image